PD-L1 antibodies-armed exosomal vaccine for enhanced cancer immunotherapy by simultaneously in situ activating T cells and blocking PD-1/PD-L1 axis - Xinyue Dai; Zhaoshuo Wang; Miao Fan; Huifang Liu; Xinjian Yang; Xueyi Wang; Xiaohan Zhou; Yunlu Dai; Jinchao Zhang; Zhenhua Li (Extracellular Vesicle)
Tumor immunotherapy significantly rewards antigen-specific T-cell responses, which have been recognized as the foundation of adaptive immune responses. However, due to the immunosuppressive effects of the tumor microenvironment, it is still hard to activate T cells in situ. Especially, antigen-specific T cell activity is further limited as tumor cells can evade T cell attack via PD-1/PD-L1 axis. During this work, we used a dendritic cells (DCs)-derivate exosome vaccine to build an immunotherapeutic system that can simultaneously mediate antigenic T cell activity by carrying T cells activating CD80 and MHC to induce humoral immunity. More importantly, in order to interrupt tumor immune escape, we also engineered anti-PD-L1 antibodies (aPD-L1) to block PD-1/PD-L1 axis at the same time. Our antigens-feeding DCs-exosomes with aPD-L1 engineering represents a promising strategy for enhanced cancer immunotherapy by robust activating T cells. The outcomes demonstrated that Exo-OVA-aPD-L1 was successful in inhibiting the growth, recurrence, and metastasis of melanoma.